A Survey on Knowledge Transfer between Knowledge-based Systems - Nyoman Karna; Iping Supriana; Nur Maulidevi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
The paper aims to clarify differences in knowledge sharing mechanisms between Knowledge-based Systems, including knowledge management system, web page-based knowledge, and expert system, in the hope that we can establish an automatic knowledge transfer between autonomous systems. This study lays the foundation for knowledge transfer mechanism where an autonomous Knowledge-based System may enhance its knowledge by using other system's knowledge. To design a knowledge transfer mechanism, the paper do a literature study by comparing three well-known protocols for knowledge sharing, OAI-PMH for knowledge management system, SPARQL for web page-based knowledge, and KQML for the expert system. The object of comparison is within three aspects, first is the ability to find another system, the second is knowledge retrieval from chosen system and third is how to add new knowledge into the system. The paper suggests that each protocol has its own strength and weakness, but when it comes to knowledge transfer, KQML covers more features. Therefore, based on this finding, the paper proposes a new model for autonomous knowledge transfer using KQML to enhance one Knowledge-based System's own knowledge.